A piezoelectric transducer made of biodegradable materials – design and properties - Mirkowska, Agnieszka; Rytlewski, Piotr; Puszczykowska, Natalia; Sołogub, Michał (Archives of Electrical Engineering (Online), 2025)
In the paper, the construction and properties of a layered piezoelectric transducer made of biodegradable materials are presented. The transducer consists of an electret layer, an elastic coating, and an outer structural layer. As the electret layer, the polylactide (PLA) foil with a thickness of 20 μm was used. The electrical properties of the foil, such as resis-tivity, relative permittivity, and charge decay, were examined. The elastic coating was made of natural rubber (NR), ensuring flexibility, while the outer structural layer was fabricated from PLA using a 3-D printing method. Two different shapes of the PLA-grid were exam-ined: hexagonal and striped, to evaluate their influence on the electromechanical perfor-mance of the device. In the paper, the model and electro-mechanical properties of the trans-ducer are presented. The electret foil was polarized using a high-voltage corona charging method. The maximal value of the piezoelectric coefficient, possible to obtain, was calcu-lated using the described model, and it is equal to d33MAX = 1.4 nC/N for a hexagonal struc-ture and 0.87 nC/N for a striped one. That corresponds to the maximal value of effective charge density qsMAX = 7.9 mC/m2 limited by Paschen’s law. The measured static value of the piezoelectric coefficient d33 was up to 280 pC/N. The presented results demonstrate the potential of biodegradable piezoelectric transducers for sustainable and environmentally friendly applications in energy harvesting and sensor technologies.